First description of the last instar larva and pupa of the aquatic crane fly Limnorimarga limonioides (Alexander, 1945) (Diptera: Limoniidae) - Podeniene, Virginija; Seo, Hong-Yul; Kim, Tae-Woo; Byun, Hye-Woo (Zootaxa, 2017)
Descriptions, illustrations and habitat characteristics are given for the previously unknown larvae and pupae of the East Palaearctic monotypic aquatic crane fly genus Limnorimarga Alexander, 1945 collected from Korea in hygropetric habitats. Diagnostic features and phylogenetic relationships are discussed.